2008
DOI: 10.1136/jech.2007.060715
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting in-hospital heat-related mortality: a multi-city case-crossover analysis

Abstract: Background: Several studies have identified strong effects of high temperatures on mortality at population level; however, individual vulnerability factors associated with heat-related in-hospital mortality are largely unknown. The objective of the study was to evaluate heat-related in-hospital mortality using a multi-city casecrossover analysis. Methods: We studied residents of four Italian cities, aged 65+ years, who died during 1997-2004. For 94 944 individuals who died in hospital and were hospitalised two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 30 publications
5
104
2
5
Order By: Relevance
“…Contrary to previous studies from the US and Europe that reported that heat-related risk of death was lower during admissions to hospital, 22,43,44 heat-related risk of death appeared to be the highest among patients in hospital in Ontario. The stronger association could be due to chance; however, it may also relate to heightened vulnerability of patients in hospital owing to their increased frailty, the insufficient cooling environment in some hospitals, or other unknown reasons.…”
Section: Comparison With Other Studiescontrasting
confidence: 52%
See 1 more Smart Citation
“…Contrary to previous studies from the US and Europe that reported that heat-related risk of death was lower during admissions to hospital, 22,43,44 heat-related risk of death appeared to be the highest among patients in hospital in Ontario. The stronger association could be due to chance; however, it may also relate to heightened vulnerability of patients in hospital owing to their increased frailty, the insufficient cooling environment in some hospitals, or other unknown reasons.…”
Section: Comparison With Other Studiescontrasting
confidence: 52%
“…Ontario consists of about 13.6 million residents (~40% of Canadian population), 44 which allows us to study the impact of temperature on a large diverse population in Canada. As well, we obtained extensive information including air pollution, influenza activity, and snowfall, which allowed for better control for confounding.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Numerous studies have been conducted to investigate the short-term effects of changes in ambient temperature on mortality, and various study designs have been used to characterize or quantify the relationships, including time series (Curriero et al 2002;Goldberg et al 2011;Hajat et al 2005;Hajat et al 2002;Huynen et al 2001;LeTertre et al 2006;Saez et al 2000) and related case-crossover designs (Bell et al 2008;Stafoggia et al 2008;Stafoggia et al 2006). The objectives of these studies were related to answering questions regarding triggering mechanisms, such as "Do the number of adverse health events increase when temperature increases or decreases?…”
Section: Epidemiology Of Ambient Temperature On Healthmentioning
confidence: 99%
“…The case-crossover design has been used mostly in epidemiological studies of the effects of air pollution on human health and in studies of acute events such as myocardial infarction, but there are also studies of the effects of temperature on human health using either the case-crossover design alone (Bell et al 2008;Stafoggia et al 2008;Stafoggia et al 2006) or both the time-series and case-crossover designs ;Medina-…”
Section: Case-crossover Studiesmentioning
confidence: 99%
“…Observational evidence indicates that regional changes in climate, particularly temperature increases, affect a diverse set of physical and biological systems in many parts of the world [1, 2], some of which are of concern for respiratory health. A rapid rise has been observed in the number of hot days, such as the 2003 heat wave where temperatures of o35uC were reached resulting in ,40 000 excess deaths across Europe, mostly for cardiopulmonary causes [5,6]. Sea levels have also started to rise as an effect of a regression of the polar ice packs.…”
mentioning
confidence: 99%